DKIS Cirebon City Communication Strategy in Tackling Hoaxes Through Instagram @cirebonsaberhoaks - Salsabiela, Safira Nissa; Burhanuddin (INTERNATIONAL PENELITI EKONOMI, SOSIAL, DAN TEKNOLOGI, 2025)
This research analyzes the communication strategy implemented by the Department of Communication, Informatics, and Statistics (DKIS) of Cirebon City in tackling the spread of hoaxes through Instagram @cirebonsaberhoaks. The widespread dissemination of false information through various digital platforms has become a serious threat to healthy public information and communication. The purpose of this research is to analyze the communication strategies and challenges faced by DKIS Cirebon City in countering hoaxes. Using a qualitative descriptive approach, data was collected through observation, interviews, and literature studies. The results show that DKIS Cirebon City implements a communication strategy consisting of three key components: focused utilization of digital platforms, a dual-focus approach (information clarification and education), and publication of anti-hoax content. Nevertheless, the program still faces significant challenges in the form of evolving technology for hoax dissemination, limited reach of a single platform, and suboptimal inter-institutional coordination. This research contributes to the development of more adaptive and innovative public communication models in tackling hoaxes at the regional level.